درجة ممارسة مديري المدارس الثانوية في محافظة إربد لمهامهم في ضوء الفكر الإداري الإسلامي من وجهة نظر المعلمين - Khimayisa, Nusayba Issa; Hijazi, Abdelhakeem Yasin; Rabab’a, Ibtisam Qassem (جامعة العلوم التطبيقية الخاصة - عمادة البحث العلمي والدراسات العليا, 2022)
هدفت الدراسة التعرف إلى درجة ممارسة مديري المدارس الثانوية في محافظة إربد لمهامهم في ضوء الفكر الإداري الإسلامي من وجهة نظر المعلمين، واعتمدت الدراسة المنهج الوصفي الارتباطي، وقام الباحثون بتطوير استبانة لقياس درجة ممارسة الفكر الإداري الإسلامي لمديري المدارس تكونت من ثلاثة مجالات، وتكون مجتمع الدراسة من جميع معلمي ومعلمات المدارس الثانوية في قصبة إربد والبالغ عددهم (2422) معلما ومعلمة، وتكونت عينة الدراسة من (365) معلما ومعلمة تم اختيارهم بالطريقة العشوائية المتيسرة، وأظهرت نتائج الدراسة أن درجة ممارسة مديري المدارس الثانوية في محافظة إربد لمهامهم في ضوء الفكر الإداري الإسلامي جاءت بدرجة مرتفعة؛ وكشفت النتائج عدم وجود فروق ذات دلالة إحصائية في درجة ممارسة مديري المدارس لمهامهم في ضوء الفكر الإداري الإسلامي تعزى لمتغيري (الجنس، والخبرة). يوصي الباحثون الاستمرار بالالتزام بالفكر الإداري الإسلامي لدى مديري بشكل عام، وذلك من خلال دراسة الأسباب والعوامل التي تعزز مستوى ممارسة الفكر الإداري ورعايتها. The study aimed to identify the degree to which secondary school principals in Irbid governorate would practice their tasks in light of Islamic administrative thought from the teachers ’point of view, and the study adopted the relational descriptive approach, and the researchers prepared a questionnaire to measure the degree of practice of Islamic administrative thought for school principals consisting of three areas. All secondary school teachers in the Irbid governorate, whose number is (2422), male and female teachers, and the study sample consisted of (365) teachers who were chosen in the available random way, and the results of the study showed that the degree to which secondary school principals in Irbid governorate practiced their tasks in light of Islamic administrative thought came High degree; The results revealed that there were no statistically significant differences in the degree of school principals ’practice of their tasks in light of Islamic management thought due to the two variables (gender, experience). The researchers recommend continuing to adhere to the Islamic managerial thought of my managers in general, by studying the causes and factors that enhance the level of practicing managerial thought and its care.
Keywords: مديرو المدارس -- المرحلة الثانوية -- الأردن